Predictors of knowledge sharing behaviour: a proposed model for the Malaysian public sector managers - Tangaraja, Gangeswari; Mohd Rasdi, Roziah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Limited studies have focused on the factors that influence knowledge sharing behaviour of managers in the Malaysian public service. Moreover, little is known about the predictors of knowledge sharing behaviour, incorporating its two dimensions i.e. knowledge donating and knowledge collecting. Therefore, the aim of this paper is to build a knowledge sharing model among managers in the Malaysian public service. Based on the reviews of relevant knowledge sharing literature and from the lens of Theory of Planned Behaviour and Self-Determination Theory, several factors were found to be potential predictors of manager’s knowledge sharing behaviour. Individual factor (attitude towards knowledge sharing), organisational factor (organisational climate) and resource factors (time availability and ICT support) are important predictors of intention to share knowledge. Intention to share knowledge and intrinsic motivational factors (knowledge self-efficacy and enjoyment in helping others) are important predictors of knowledge sharing behaviour (knowledge donating and knowledge collecting).